Pengaruh Macam dan Ketebalan Mulsa Organik Terhadap Populasi Gulma dan Hasil Melon (Cucumis melo L.) - Setiawan, Agus Nugroho; Utari, Lilik; Oktarini, Metasia (PLANTA TROPIKA: Jurnal Agrosains (Journal of Agro Science), 2005)
The research to observe the effect of the kinds and thickness of organic mulch toward the population of weeds and melon yield was conducted in Wringin, Purwobinangun, Pakem, Sleman District of Yogyakarta, at February up to May 2004. The research site has the 500 m above sea level altitude and the Regosol soil type. The field experiment was arranged in a single factor Randomized Completely Block Design with three blocks as replications. The treatments of mulch kinds consisted of 8 levels which are: no mulch application, plastic mulch, straw mulch with 4 cm, 8 cm, and 12 cm thickness, bamboo leaves mulch with 4 cm, 8 cm, and 12 cm thickness. The effect of treatments on weeds population suppression, melon growth and yield were observed during the growth period. The result showed that the bamboo leaves mulch with 8 cm thickness and plastic mulch significantly suppressed weeds population until 67 days after planting in compared with the other treatments. Straw mulch and bamboo leaves mulch significantly increased the component of melon yield, but the kind and thickness of organic mulch was not significantly affected the growth and yield of melon.